Association of Disease Activity with Serum and Tear IL-2 Levels in Behc, et Disease - Turkcuoglu, Peykan; Arat, Yonca Ozkan; Kan, Emrah; Kan, Elif Kilic; Chaudhry, Imtiaz A.; Koca, Suleyman; Ilhan, Nevin (Taylor & Francis Inc, 2016)
Purpose: To investigate the association of Behcet disease activity with serum and tear interleukin-2 levels. Methods: The study was designed as a prospective case control study. The study population consisted of 45 patients with Behcet disease and 24 age and sex-matched healthy participants. Behcet disease patients were classified as active (24 patients) or inactive (21 patients) according to disease activity. Serum and tear interleukin-2 levels were determined using the enzyme-linked immunosorbent assay method. Results: The mean serum and tear interleukin-2 levels of the active disease, inactive disease, and control groups were 17.04 +/- 5.02 and 32.61 +/- 16.53 pg/mL; 15.20 +/- 4.68 and 29.61 +/- 8.30 pg/mL; and 14.22 +/- 4.18 and 28.89 +/- 8.73 pg/mL, respectively. There was no statistically significant difference between the groups with respect to all measured data. Conclusions: There was no significant difference in serum or tear IL-2 levels between Behcet patients and controls; there was no association of disease activity with serum and tear IL-2 levels.
Keywords: Behcet; Behcet's disease; interleukin; interleukin-2; tear interleukin